E-COMMERCE DURING CORONAVIRUS: Bachelor of Science in Business Administration - Garry Alfonsius (Universal Institute of Professional Management, 2020)
Today e-commerce always gets more attention from people because the coronavirus we cannot go out from our house. So, we have conclusion to buy from e-commerce it will make easy than we should go outside. But sometimes many people got addict to buy from e-commerce. When they open the site of e-commerce many people always give a lot of time to search what they want and waste their time to scroll it. E-commerce trends in coronavirus predicament as well as how imminent progress in e-commerce that might affect consumer behavior in future. E- commerce is become a substitute source and considered top in this condition, and e-retailers provides goods that usually consumers bought in superstore traditionally. Now coronavirus have an impact on whole of e-commerce.